U źródeł leseferyzmu i subiektywizmu myśli Murraya Rothbarda. Arystoteles, Święty Tomasz, hiszpańscy scholastycy, John Locke i Fryderyk Bastiat jako źródła inspiracji - Wojtyszyn, Radosław (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
The subject of this article are origins of the subjectivist view of the economic activity of man, and pre-classic themes of political economy, which are the inspirations for Murray Newton Rothbard and his thought of anarcho-capitalism. These issues, being so rarely subject to scientific interest, are crucial point of reference for classical and neoclassical economics, and laissez-faire in general. Specific influence of natural law on the sphere of economic activity and human condition also implies a broader view of the role of state institutions in the thought of Aristotle, Thomas Aquinas, the scholastics of the Salamanca, John Locke and Frederic Bastiat, who combined the above-mentioned laws of nature and tradition of classical economics with subjectivity, so important in Austrian School of Economics and in anarcho-capitalist thought of Murray Newton Rothbard
Keywords: św. Tomasz z Akwinu; scholastycy hiszpańscy; Locke John (1632-1704); Bastiat, Frédéric (1801-1850); wymiana; subiektywizm; kredyty; pieniądz; prawo własności